2020
DOI: 10.1007/s10973-020-09284-9
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic analysis of the aluminum titanate (Al2TiO5) reaction-sintering from alumina and titania, properties and effect of alumina particle size

Abstract: Aluminum titanate Al 2 TiO 5 materials were successfully processed from different fine commercial powders and characterized. Particularly, two calcined aluminas were compared through a multitechnique approach including differential thermal analysis and dilatometry together with structural, microestructural, and mechanical characterization. This allowed the description of all the thermochemical processes during thermal treatment. Developed phases were established. Relatively dense ceramics were obtained, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The AT grains in the A-40AT composites exhibited a distinct irregular shape and heterogeneity in size distribution, as indicated by the arrows in Figure 3e,g. Some AT grains clustered together as a submatrix (4-6 µm), where alumina grains were separated and surrounded by AT grains; a similar phenomenon was also reported in another study [38]. The Al 2 O 3 grain size evidently decreased as the AT content increased owing to the inhibiting effect of second-phase AT particles on the Al 2 O 3 matrix grain growth.…”
Section: Phase Composition and Microstructuresupporting
confidence: 83%
See 3 more Smart Citations
“…The AT grains in the A-40AT composites exhibited a distinct irregular shape and heterogeneity in size distribution, as indicated by the arrows in Figure 3e,g. Some AT grains clustered together as a submatrix (4-6 µm), where alumina grains were separated and surrounded by AT grains; a similar phenomenon was also reported in another study [38]. The Al 2 O 3 grain size evidently decreased as the AT content increased owing to the inhibiting effect of second-phase AT particles on the Al 2 O 3 matrix grain growth.…”
Section: Phase Composition and Microstructuresupporting
confidence: 83%
“…A previous study [37] investigated the dynamic phase formation in the temperature range of 20-1400 • C for the fabrication of A-AT samples by means of neutron diffraction and differential thermal analysis. The results showed that the formation of AT in A-AT samples occurred at temperatures exceeding 1310 • C by the reaction sintering of the Al 2 O 3 and TiO 2 mixture; TiO 2 disappeared at 1370 • C. Violini et al [38] reported that in the two-step reaction sintering of initial powders (alumina and titania), the formation of AT started at 1380 and ended at 1440 • C. In our work, the sintering temperature 1450 • C ensured the complete formation of AT. However, in the XRD profiles of the A-10AT(1550) and A-40AT(1550) composites, in addition to the main peaks of the Al 2 O 3 and AT phases, a small peak of TiO 2 (rutile) phase was detected at around 2θ = 7.6 • (hkl = 110).…”
Section: Phase Composition and Microstructurementioning
confidence: 98%
See 2 more Smart Citations
“…The curve of the LC-TiO 𝑥 -3 presented a clear decrease in slope at about 1300 • C, which was not observed for the other batches, indicating a possible phase transformation within the material, for example, the formation of aluminum titanate. 20,34 A similar trend was not observed for the LC-TiO 𝑥 batch, Finally, the thermal expansion coefficients 𝛼 were calculated from the dilatometry results in two distinct temperature ranges (see Table 5). Overall, the castables showed almost the same behavior, except at temperatures close to T dL max .…”
Section: Open Porosity (%)supporting
confidence: 56%